2017
DOI: 10.1002/adsc.201700546
|View full text |Cite
|
Sign up to set email alerts
|

A Copper‐Catalyzed Cascade Approach for the Synthesis of Dibenzo[b,f]1,8‐naphthyridine Derivatives

Abstract: The synthesis of some dibenzo[b,f]‐[1,8]naphthyridine derivatives in a cascade manner is reported. The reaction includes a Knovenagel condensation, the insertion of a nitrile and an alkyne into an N–H bond and an oxidation/oxidative C–C bond cleavage sequence in the presence of copper iodide. The key 1,8‐naphthyridine core was constructed in a cascade manner during the course of the reaction itself which allows diverse dibenzo[b,f]‐[1,8]naphthyridine derivatives to be readily prepared.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a continuation of our research efforts in exploring additional synthetic aspects of 2-iodobezylcyanide surrogates for the construction of various valuable heterocyles and based on clues provided in literature cited above (Scheme , eqs 1–3), we hypothesized that it might be possible to prepare 2-aryl-3-cyanobenzofuran derivatives through the in situ generation of the hydroxyl intermediate III from iodoarene, using 2-iodobenzylcyanides 2a and benzaldehyde 1a as starting materials (Scheme , eq 4). This might be achieved through Knoevenagel condensation, aryl hydroxylation, oxa-Michael addition, and aromatization reactions in a cascade manner by utilizing some previously reported copper-mediating protocols .…”
Section: Introductionmentioning
confidence: 99%
“…In a continuation of our research efforts in exploring additional synthetic aspects of 2-iodobezylcyanide surrogates for the construction of various valuable heterocyles and based on clues provided in literature cited above (Scheme , eqs 1–3), we hypothesized that it might be possible to prepare 2-aryl-3-cyanobenzofuran derivatives through the in situ generation of the hydroxyl intermediate III from iodoarene, using 2-iodobenzylcyanides 2a and benzaldehyde 1a as starting materials (Scheme , eq 4). This might be achieved through Knoevenagel condensation, aryl hydroxylation, oxa-Michael addition, and aromatization reactions in a cascade manner by utilizing some previously reported copper-mediating protocols .…”
Section: Introductionmentioning
confidence: 99%
“…Demir et al reported that Ph 3 PAuCl and Zn­(ClO 4 ) 2 cooperatively catalyzed tandem hydroamination/cyclization reaction of electron-deficient cyanoalkynes with amines to give 2-aminopyrroles as the main products with a different cyclization pattern (Scheme c) . Yao et al described the construction of 1,8-naphthyridine core through a sequential intramolecular insertion of a nitrile and an alkyne into an N–H bond of amides in the presence of CuI and base (Scheme d) …”
mentioning
confidence: 99%
“…Replacement of Y­[N­(SiMe 3 ) 2 ] 3 with other rare-earth-metal sources, such as Y­(OTf) 3 or YCl 3 , resulted in no reaction (entries 15 and 16). In addition, CuI showed no catalytic activity even in the presence of base (entry 17) …”
mentioning
confidence: 99%
See 2 more Smart Citations